ANALISIS YURIDIS PERJANJIAN JUAL BELI TANAH DENGAN PENJUAL YANG MENGHILANG SEBELUM PROSES BALIK NAMA - Anastasia Resa Andriani (Pojok Publisher, 2025)
Land is something that cannot be separated from human life, because it has various functions for community life. Therefore, many people make purchases and sales with land as the object. As stated in Decision 23/Pdt/.G/2021/Pn.Pli when the Applicant asked the Court to assist the Applicant in providing legal certainty and accountability to the Defendant for the land owned by the Applicant which had not been changed for a long time. This study aims to determine the conformity between the Decision of the Panel of Judges and related laws and regulations and the legal consequences for the parties in this case. The research method used in this case study is a normative legal approach, by reviewing and examining secondary data such as the Decision of the Pelaihari District Court, the Civil Code, the Basic Agrarian Law, and other library materials such as books and journals to analyze related decisions. This study also uses a descriptive analytical method, which aims to describe or describe the object of research based on the materials that have been collected. Based on the research results, it can be concluded that land registration according to UUPA is an obligation to obtain legal certainty, as regulated in Article 19 and Article 23 paragraph (1) and (2) UUPA. In the context of the Civil Code, legal certainty for the plaintiff has not been fulfilled because the name change process has not been carried out, according to Article 1239 and Article 1241 of the Civil Code, which in its implementation is supported by PP Number 24 of 1997 concerning Land Registration.